2018
DOI: 10.18632/oncotarget.26042
|View full text |Cite
|
Sign up to set email alerts
|

The close relationship between heparanase and epithelial mesenchymal transition in gastric signet-ring cell adenocarcinoma

Abstract: Heparanase (HPSE), a heparan sulfate-specific endo-β-D-glucuronidase, plays an important role in tumor cell metastasis through the degradation of extracellular matrix heparan sulfate proteoglycans. Suramin, a polysulfonated naphthylurea, is an inhibitor of HPSE with suramin analogues. Our objective was to analyze the HPSE involvement in gastric signet ring cell adenocarcinoma (SRCA) invasion. High expression of HPSE mRNA and protein was found in the tumor and in ascites of SRCA as well as in KATO-III cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…The characteristics of SRCA are its resistance to chemotherapy (2), tissues fibrosis and peritoneal invasion (3). Recently we reported the upregulated expression of heparanase in SRCA, which is involved in the acquisition of the mesenchymal phenotype and tumor cell malignancy (4). In the present study, it was also revealed that the epithelial-mesenchymal transition (EMT) process could be inhibited by suramin, an heparanase inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of SRCA are its resistance to chemotherapy (2), tissues fibrosis and peritoneal invasion (3). Recently we reported the upregulated expression of heparanase in SRCA, which is involved in the acquisition of the mesenchymal phenotype and tumor cell malignancy (4). In the present study, it was also revealed that the epithelial-mesenchymal transition (EMT) process could be inhibited by suramin, an heparanase inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Heparanase degrades heparan sulfate chains and it contributes to ECM remodeling. Heparanase is eventually involved in ECM remodeling and EMT [ 44 , 45 ]. When heparanase is downregulated, it can inhibit tumor metastasis [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heparanase is eventually involved in ECM remodeling and EMT [ 44 , 45 ]. When heparanase is downregulated, it can inhibit tumor metastasis [ 44 , 45 ]. Previous studies from our laboratories showed that MMP-14 activity was inhibited by lumican in melanoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Examples include suramin for prostate cancer [71], inhibition of inducible nitric oxide synthase for triple negative breast cancer [72], and chitosan as a nanocarrier for SN38 and Snail-specific siRNA in prostate cancer cells [73]. These approaches have been shown to downregulate Twist [72], Slug [72,74], and Snail [72,73]. Furthermore, the crosstalk between tumour cells undergoing EMT and immune cells in the tumour microenvironment has garnered increasing interest and may provide possibilities for combining immunotherapy with EMTtargeted therapy or for using EMT score as a potential predictive marker for immunotherapy response [75,76].…”
Section: Discussionmentioning
confidence: 99%